Evaluasi Hubungan Profitabilitas, Leverage, dan Capital Intensity terhadap Tax Avoidance - Fatin, Sekar Fajrina; Machddar, Nera Marinda (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Tax avoidance erodes state revenues, necessitating a critical analysis of its driving factors. This study examines the impact of profitability, leverage, and capital intensity on tax avoidance in manufacturing companies listed on the Indonesia Stock Exchange (IDX), using multiple linear regression with secondary data. The results show that profitability and capital intensity have a significant negative effect on tax avoidance, while leverage is insignificant. These findings challenge conventional assumptions and provide insights into ethical tax management strategies, albeit limited to the manufacturing sector.